P3.360 An Assessment of the Knowledge and Practical Skills in Using Male Condoms Among the General Public. (13th July 2013) - Kay, S L; Radcliffe, K
Abstract : Background: Condoms decrease sexually transmitted infection(STI) transmission, good evidence supports this, if used correctly. This study investigates individuals understanding of the correct use of male latex condoms. Methods: Random individuals completed a questionnaire and were requested to conduct an observed demonstration of condom application, marked against criteria from British Association for Sexual Health and HIV(BASHH) guide for condom use and Centers for Disease Control and prevention(CDC) Condom fact sheet. Results: 127 responders, 45 participants in the observed demonstration(57%males, 46%females, age 12–66) 100% believed they used condoms correctly, 68% were self taught. 100% knew condoms were barrier contraception. 67% indicated condoms protection against all STIs and 5% indicated no STI protection: 11% gonorrhoea and Chlamydia only, 10% HSV and warts only and 7% HIV only. 7% felt condoms decreased STI transmission during oral sex and 10% during anal sex(100% of men who have sex with men) During observed demonstration, 33% correctly applied a condom. Mistakes: not squeezing air from condom, unrolling before applying and condom contact when opening. Factors stated to increase latex condom splitting: 25% penis size, 22% sexual vigour, 7% certain lubricants, 46% unsure(25% admitted to doubling condoms once since coitarche, all unaware of risk) 38% believed condoms not required throughout intercourse, 100% of these believed STI transmission was decreased if worn at the end. Conclusion: Perceived good condom technique, however, practical adherence to guidance is poor(particularly younger cohorts) Inadequate heterosexual awareness of STI transmission and prevention during oral and anal intercourse. Poor understanding of condom STI prevention, risks for condom splitting and timing of condom use. Good quality sexual education to include male condoms is important. Age of education is crucial capturing individuals before and timely to coitarche. Self teaching is common and requires quality accessible material. Opportunistic teaching is required, condom use competence should not be assumed.